An original concept for the synthesis of an oxide coating: The film boiling process. Issue 5 (May 2021) - Besnard, C.; Allemand, A.; David, P.; Léon, J.F.; Maillé, L.
Abstract: The film boiling chemical vapor process is an original and rapid synthesis method for ceramic coatings and composites. This work reports the deposition of silica coating from tetraethyl orthosilicate (TEOS) by film boiling chemical vapor process. Experiments were carried out under atmospheric pressure between 900 °C and 1100 °C. Several modifications of the experimental setup were made in order to allow a better thermal monitoring. Silica coatings were fast synthetized: several microns per minute. An activation energy of 209 kJ/mol ± 20 was deduced. The structure and microstructure of the oxide coating were characterized by Optical Microscopy, Scanning Electron Microscopy, Energy Dispersive Spectroscopy, Electron Probe MicroAnalyzer, Fourier-Transform InfraRed spectrometery and X-ray diffraction.